2015
DOI: 10.1155/2015/232836
|View full text |Cite
|
Sign up to set email alerts
|

Direct Effects of (−)-Epicatechin and Procyanidin B2 on the Respiration of Rat Heart Mitochondria

Abstract: Flavonol (−)-epicatechin and its derived dimer procyanidin B2, present in high amounts in cocoa products, have been shown to exert beneficial effects on the heart and cardiovascular system; however, their mechanism of action has not been fully elucidated. We studied effects of (−)-epicatechin and procyanidin B2 on the oxidative phosphorylation of isolated rat heart mitochondria. (−)-Epicatechin and procyanidin B2 had stimulating effect (up to 30% compared to control) on substrate-driven (State 2) mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
2
32
1
Order By: Relevance
“…Early studies demonstrated that monomeric cocoa catechin promotes β-cell stability through up-regulating the expression of key genes that encode antioxidant and mitochondrial respiratory complex proteins [58]. In addition, other studies shown that epicatechin and procyanidin B2 directly influence mitochondrial functions by reducing release of cytochrome c in isolated rat heart [59]. In line with these reports, our results demonstrated that C, EC, PB7, PB6, PB3, and PB1 ameliorated Dex-induced mitochondrial deficits in 3T3-L1 adipocytes, via improving mitochondrial biogenesis, dynamics, transmembrane potential, and antioxidant defenses.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies demonstrated that monomeric cocoa catechin promotes β-cell stability through up-regulating the expression of key genes that encode antioxidant and mitochondrial respiratory complex proteins [58]. In addition, other studies shown that epicatechin and procyanidin B2 directly influence mitochondrial functions by reducing release of cytochrome c in isolated rat heart [59]. In line with these reports, our results demonstrated that C, EC, PB7, PB6, PB3, and PB1 ameliorated Dex-induced mitochondrial deficits in 3T3-L1 adipocytes, via improving mitochondrial biogenesis, dynamics, transmembrane potential, and antioxidant defenses.…”
Section: Discussionmentioning
confidence: 99%
“…However, in support of the second hypothesis, polyphenol have been in many contexts shown to directly affect mitochondrial activity and stimulate mitochondrial ATP production. Both epicatechin and Procyanidin B2 possess uncoupling effect on oxidative phosphorylation in cardiac mitochondria [ 63 ], suppressing activity of pyruvate and malate oxidation and stimulating fatty acid β-oxidation. Comparing our metabolic profiles with those described for murine HFs in different stages of the hair cycle [ 55 ], it seems more likely that the mitochondrial activity itself is responsible for inducing the early anagen aspect of AAE-treated HFs.…”
Section: Discussionmentioning
confidence: 99%
“…In tumor cells, mitochondria are usually hyperpolarized, and their membrane potential reaches 220 mV [186,187] making them resistant to cell death signaling. Our group evaluated direct effects of selected flavonoids on the functions of cardiac mitochondria respiring on pyruvate and malate as substrates [188][189][190][191]. The results demonstrated that (-)-epicatechin [190,191], procyanidin B2 [190,191], hyperoside [189,190], quercetin [189,190], quercitrin [189,190] and rutin [189,190] uncoupled oxidation from phosphorylation.…”
Section: Effects Of Flavonoids On Mitochondrial Functionsmentioning
confidence: 99%